Early Diverging and Core Bromelioideae (Bromeliaceae) Reveal Contrasting Patterns of Genome Size Evolution and Polyploidy - Paule, Juraj; Heller, Sascha; Maciel, Jefferson Rodrigues; Monteiro, Raquel F.; Leme, Elton M. C.; Zizka, Georg (Frontiers in Plant Science, 2020)
The subfamily Bromelioideae is one of the most diverse groups among the neotropical Bromeliaceae. Previously, key innovations have been identified which account for the extraordinary radiation and species richness of this subfamily, especially in the so-called core Bromelioideae. However, in order to extend our understanding of the evolutionary mechanisms, the genomic mechanisms (e.g. polyploidy, dysploidy) that potentially underlie this accelerated speciation also need to be tested. Here, using PI and DAPI staining and flow cytometry we estimated genome size and GC content of 231 plants covering 30 genera and 165 species and combined it with published data. The evolutionary and ecological significance of all three genomic characters was tested within a previously generated dated phylogenetic framework using ancestral state reconstructions, comparative phylogenetic methods, and multiple regressions with climatic variables. The absolute genome size (2C) of Bromelioideae varied between 0.59 and 4.11 pg, and the GC content ranged between 36.73 and 41.43%. The monoploid genome sizes (Cx) differed significantly between core and early diverging lineages. The occurrence of dysploidy and polyploidy was, with few exceptions, limited to the phylogenetically isolated early diverging tank-less lineages. For Cx and GC content Ornstein-Uhlenbeck models outperformed the Brownian motion models suggesting adaptive potential linked to the temperature conditions. 2C values revealed different rates of evolution in core and early diverging lineages also related to climatic conditions. Our results suggest that polyploidy is not associated with higher net diversification and fast radiation in core bromelioids. On the other hand, although coupled with higher extinction rates, dysploidy, polyploidy, and resulting genomic reorganizations might have played a role in the survival of the early diverging bromelioids in hot and arid environments.